Understanding the Effectiveness of Phospholane Electrolyte Additives in Lithium‐Ion Batteries under High‐Voltage Conditions. Issue 5 (10th March 2021) - Wölke, Christian; Diddens, Diddo; Heidrich, Bastian; Winter, Martin; Cekic‐Laskovic, Isidora
Abstract: Six phospholane functional electrolyte additives that enable the formation of an effective cathode electrolyte interphase (CEI) via a polymerization reaction on the electrode surface were designed, synthesized, and comparatively analyzed by means of complementary experimental and computational methods in order to understand their mode of action in NMC111‖graphite battery cells under high voltage conditions. Two reaction mechanisms, namely a phosphate‐based and a phosphonate‐based mechanism, were postulated and, based on systematic analysis, the phosphate mechanism was identified as the more likely. Direct correlation of the phospholane's structural features and relevant properties impacting the direct correlation of the phospholane's structural features and relevant properties impacting the overall cycling performance of NMC111‖graphite cells, as depicted by capacity retention, stands for a vital example approach towards identifying promising electrolyte components for advanced, targeted applications. Abstract : Small change, big influence : Six phospholane electrolyte additives, featuring incremental changes to their structure, are synthesized for the first time and analyzed via complementary experimental and computational methods to understand their performance in NMC111‖graphite battery cells under high voltage conditions. The computational results could be directly correlated to the overall cycling performance, resulting in elucidation and proposition of a reaction mechanism.